CEO Influencer: estrategias de interactividad de los directores ejecutivos de América Latina en LinkedIn y su impacto en el engagement - Saavedra, Giancarlo (2025)
Several studies on CEO communication via social media have highlighted the need to assess the fulfillment of the theoretical promise of dialogue. This paper analyzes the interactivity strategies employed by Latin American CEOs on LinkedIn and their impact on engagement. The research focuses on three variables: general communication approaches, communication resources, and level of engagement generated by CEO posts. CEOs were selected based on the América Economía 500 ranking. Of the 327 CEOs identified on LinkedIn, 7 461 posts from 244 active accounts were analyzed. The findings reveals several predominant trends: most CEOs adopt an informative approach and achieve higher levels of engagement. They primarily use expository resources such as text and graphics, with limited use of interactive resources such as participatory ones. Overall, Latin American CEOs on LinkedIn employ a monologic interactivity strategy, characterized by informative posts and the use of expository resources. However, engagement improves when the diversity of communication resources increases. This study offers tools to maximize CEOs’ impact on LinkedIn reputation management. It also proposes a typology of three CEO communication profiles: Disseminating CEOs, empowering CEOs, and interactive CEOs.